Effect of cathode waste material concentration in conductive paint coating - N.S.W. Zulkefeli; W.M.I.W. Ismail; M.K.A.A. Razab; M.N. Masri (Universiti Malaysia Kelantan, 2016)
The conductive paint coating can be used to control the electromagnetic interference in electronic application. Conductive paint coating was made by mixing the epoxy and hardener with cathode waste material (CWM) in order to manipulate their properties. In this study, the conductivity and the thickness of the paint has been studied. The thickness of conductive paint coating was depends on the agglomeration of CWM content. The increasing of wt% of CWM, the thickness of paint is increasing. Bruker D2Phaser X-Ray diffraction has been used in order to get the phase analysis of the paint before and after soaking into Potassium Hydroxide solution.